PENGARUH KEMAMPUAN KERJA DAN TUNJANGAN KESEJAHTERAAN TERHADAP PRESTASI KERJA KARYAWAN - Novrinando, Heru; Onsardi, Onsardi (UM. Bengkulu, 2025)
The aim of the study was to determine the effect of ability and welfare benefits on work performance of employees of the Tirta Hidayah Regional Public Company, Bengkulu City. The research was conducted at the Tirta Hidayah Regional Public Company, Bengkulu City. The research respondents were 33 permanent employees of the company, data collection was through questionnaires and observation, while data analysis was carried out using multiple linear regression. The results of the study show that work ability has a positive and significant effect on employee performance. Welfare benefits have a positive and significant effect on employee performance. Work ability and welfare benefits have a positive and significant effect on employee performance. Keywords : work ability, welfare allowances, work performance